2023
DOI: 10.1001/jamanetworkopen.2022.50613
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Melanocytic Pathology Assessment Tool and Hierarchy for Diagnosis Classification Schema for Melanocytic Lesions

Abstract: ImportanceA standardized pathology classification system for melanocytic lesions is needed to aid both pathologists and clinicians in cataloging currently existing diverse terminologies and in the diagnosis and treatment of patients. The Melanocytic Pathology Assessment Tool and Hierarchy for Diagnosis (MPATH-Dx) has been developed for this purpose.ObjectiveTo revise the MPATH-Dx version 1.0 classification tool, using feedback from dermatopathologists participating in the National Institutes of Health–funded R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Finally, the MPATH-Dx schema was recently revised into an MPATH-Dx 2.0 version, whereby most moderate atypias do not require a re-excision. 13 As new data emerges 22 and the field evolves, the MPATH-Dx (and the educational tutorial) will need to be updated accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the MPATH-Dx schema was recently revised into an MPATH-Dx 2.0 version, whereby most moderate atypias do not require a re-excision. 13 As new data emerges 22 and the field evolves, the MPATH-Dx (and the educational tutorial) will need to be updated accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…6 Over the past decade, the MPATH-Dx has been successfully used in research. 7 , 8 , 9 , 10 , 11 The International Melanoma Pathology Study Group has evaluated 12 and helped refine the MPATH-Dx 13 , the schema is included in dermatopathology textbooks 14 , 15 and mentioned in the World Health Organization Classification of Skin Tumours, 16 , 17 and interest of pathologists around the globe has been piqued. 18 US dermatopathologists have recognized the value of a standardized system for categorizing melanocytic skin lesions for patient management and research, and have reported willingness to embrace the MPATH-Dx concept in their own practices to improve communication and patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Like problematic cases, all Spitz tumors could be prognostically assessed for their inherent clinical risk, that is, the probability of an adverse event occurring [40,75,76]. According to the TMB of each individual neoplasm, in fact, all Spitz tumors carry some level of risk, including lesions diagnosed as "Spitz nevi", which also imply a risk, albeit very small [67,72,85]. The level of risk could be estimated as very low/minimal and clinically negligible, low, moderate, high or very high, and clinically relevant (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…4 As a result of more routine utilization of genomics, it has become apparent that there is a spectrum of BRAF and NRAS mutated melanocytic neoplasms, ranging from benign to malignant, that can closely mimic Spitz neoplasms morphologically. 2 In this study, we were specifically interested in whether expert pathologists could distinguish between benign and intermediate-grade melanocytic neoplasms with spitzoid morphology and a BRAF activating point mutation, that is, tumors, in general, mapping to MPATH-Dx V2.0 class II 5 from comparable true Spitz neoplasms. To assess this, we invited expert melanoma pathologists from the International Melanoma Pathology Study Group to evaluate and diagnose a series of 54 cases consisting of both BRAF-mutated nevi/tumors with spitzoid features (BRAF mutated and morphologically spitzoid [BAMS] nevi/tumors) and true fusion or HRAS mutated Spitz tumors (STs).…”
mentioning
confidence: 99%